Cleanliness, Health, Safety, and Environment Sustainability (CHSE) Implementation in Housekeeping Department - Ni Kadek Anik Evryastuti; I Gusti Agung Mas Krisna Komala Sari; I Ketut Suarja; I Ketut Suja; Ni Made Sudarmini (International Journal of Travel, Hospitality and Events, 2022)
ABSTRACT Purpose: This study was conducted to determine the application of SOP (standard operating procedures) in the Housekeeping Department before the Covid-19 pandemic and after being certified CHSE (cleanliness, health, safety, and environmental sustainability at the Renaissance Bali Uluwatu Resort & Spa Hotel, Bali, Indonesia. Research methods: The study uses a qualitative descriptive method using narrative analysis of data sources. The interviews and the informants are addressed were executive housekeepers, housekeeping supervisors, and housekeeping staff at the Renaissance Bali Uluwatu Resort & Spa Hotel. Results and discussion: There was a significant difference between the application of SOP in the Housekeeping Department (room attendant, public area attendant, and laundry station) before the covid-19 pandemic and after being certified CHSE at the Renaissance Bali Uluwatu Resort & Spa Hotel. Implication: There are significant differences in the application of SOP at the Renaissance Bali Uluwatu Resort & Spa Hotel after being certified CHSE in the room. Keywords: standard operating procedures, CHSE, housekeeping department.